PENGARUH PENGGUNAAN MEDIA GRAFIS GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS AL- WASHLIYAH SORKAM - Mita Wulandari; Hamdi Abdul Karim (CV. ADIBA ASIHA AMIRA, 2024)
The purpose of this study was to determine the effect of using graphic image media on student learning outcomes at MTs Al-Washliyah Sorkam. This study is a quantitative study with a research design that uses Quasi Experiment. The sample of this study was grade VII students at MTs Al-Washliyah Sorkam with a sample size of 60 students. The sample of the study was class VII A Experiment using graphic image media and class VII B Control with conventional methods, data analysis techniques using hypothesis testing with paired sample tests. The results showed that there was a significant effect on the use of graphic image media on student learning outcomes in the subject of aqidah akhlak at MTs Al-Washliyah Sorkam class VII A. As these results prove that the value of the experimental class Sig (2-tailed) = 0.000 while alpha (0.000 <0.05), with an average value using graphic image media of 72.83.